Africa, Laboratory Equipment and COVID-19 Response - Bezuidenhout, Louise (My University, 2020)
As the world struggles to address the COVID-19 crisis, attention increasingly turns to laboratories and the crucial role that they play in diagnostics and research. A rising number of reports from multiple countries detail these problems: lack of laboratories, reagents, technicians, and equipment form bottlenecks in both diagnosis and the race for a viable vaccine. As COVID-19 cases start to appear on the African continent, questions about laboratory capacity become even more pertinent. The 2014–2016 Ebola pandemic clearly illustrated the challenges of managing pandemic responses in contexts with under resourced health infrastructures and strained laboratory testing capacity (Bell et al. 2016). In the case of the Ebola pandemic, these shortfalls were offset by a significant and sustained international response that brought equipment, testing capabilities, and streamlined supply chains into affected areas.
Keywords: Laboratory Equipment; Africa; COVID-19